Aflatoxin B1 Induces Reactive Oxygen Species-Mediated Autophagy and Extracellular Trap Formation in Macrophages - An, Yanan; Shi, Xiaochen; Tang, Xudong; Wang, Yang; Shen, Fengge; Zhang, Qiaoli; Wang, Chao; Jiang, Mingguo; Liu, Mingyuan; Yu, Lu (Frontiers in Cellular and Infection Microbiology, 2017)
Aflatoxins are a group of highly toxic mycotoxins with high carcinogenicity that are commonly found in foods. Aflatoxin B1 (AFB1) is the most toxic member of the aflatoxin family. A recent study reported that AFB1 can induce autophagy, but whether AFB1 can induce extracellular traps (ETs) and the relationships among innate immune responses, reactive oxygen species (ROS), and autophagy and the ETs induced by AFB1 remain unknown. Here, we demonstrated that AFB1 induced a complete autophagic process in macrophages (MΦ) (THP-1 cells and RAW264.7 cells). In addition, AFB1 induced the generation of MΦ ETs (METs) in a dose-dependent manner. In particular, the formation of METs significantly reduced the AFB1 content. Further analysis using specific inhibitors showed that the inhibition of either autophagy or ROS prevented MET formation caused by AFB1, indicating that autophagy and ROS were required for AFB1-induced MET formation. The inhibition of ROS prevented autophagy, indicating that ROS generation occurred upstream of AFB1-induced autophagy. Taken together, these data suggest that AFB1 induces ROS-mediated autophagy and ETs formation and an M1 phenotype in MΦ.